Research on the effects of GLP-1 receptor agonists in treating cognitive dysfunction and gait disorders in elderly patients with diabetes - Yang, Yang; Chen, Lifeng; Zhang, Yanjun; Fu, Wenqian; Liu, Dandan; Jiang, Tianyu (Frontiers in Pharmacology, 2025)
Elderly patients with Type 2 Diabetes Mellitus (T2DM) often experience cognitive dysfunction and gait disorders, which significantly affect their quality of life and daily function. Glucagon-like peptide-1 receptor agonists (GLP-1RAs), known as “wonder drugs for weight loss,” have shown potential not only for glycemic control but also for improving cognitive function and gait disturbances. GLP-1RAs may exert their effects through various mechanisms, including promoting neurogenesis and synaptic plasticity in the brain, as well as reducing neuroinflammation, thereby improving cognitive and gait impairments either directly or indirectly. This review aims to explore the role of GLP-1RAs in the treatment of diabetes-related cognitive dysfunction and gait disturbances, as well as their potential mechanisms, providing a theoretical basis for clinical treatment.